2011
DOI: 10.1007/s12555-011-0207-2
|View full text |Cite
|
Sign up to set email alerts
|

Particle swarm optimization-based fixed-structure ℋ ∞ control design

Abstract: In this paper, a new robust fixed-structure H ∞ controller design based on the Particle Swarm Optimization (PSO) technique is proposed. The optimization-based structured synthesis problem is formulated and solved by a constrained PSO algorithm. In the proposed approach, the H ∞ controller's structure is selectable. PI and PID controller structures are especially adopted. The case study of an electrical DC drive benchmark is adopted to illustrate the efficiency and viability of the proposed control approach. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The cost functions of problem (23) are chosen, relative to each controlled variable ϕ , θ and ψ , as the integral absolute error (IAE) criteria (Bouallègue et al, 2011, 2012a, 2012b), which are defined with the generic form as follows:…”
Section: Optimization-based Control Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost functions of problem (23) are chosen, relative to each controlled variable ϕ , θ and ψ , as the integral absolute error (IAE) criteria (Bouallègue et al, 2011, 2012a, 2012b), which are defined with the generic form as follows:…”
Section: Optimization-based Control Problem Formulationmentioning
confidence: 99%
“…The convergence and parameters selection of the PSO algorithm are proved (Clerc and Kennedy, 2002). The PSO theory has been enormously successful in various industrial domains, but more significantly in control engineering design as shown in Bouallègue et al (2011, 2012a, 2012b).…”
Section: Proposed Particle Swarm Optimization Algorithmsmentioning
confidence: 99%
“…It has been used across a wide range of engineering applications. These applications can be summarized around domains of robotics, image and signal processing, electronic circuits design, communication networks, but more especially the domain of plant control design, as shown in [2][3][4][5][6].…”
Section: Overviewmentioning
confidence: 99%
“…Michalewicz, Dasgupta, Riche and Schoenauer [12] augmented the cost function with penalty functions to handle the optimization problems subject to a set of constraints. Soufiene Bouall egue, Joseph Hagg ege and Mohamed Benrejeb [13] applied the above method to fixed-structure H 1 controller design. However, the values of the penalty parameters are usually difficult to choose.…”
Section: Introductionmentioning
confidence: 99%